TOPOGRAPHIC MAPPING, TEMPERATURE DISTRIBUTION, AND pH OF HOT SPRINGS IN PADANG GANTING, TANAH DATAR, WEST SUMATRA: A PRELIMINARY STUDY - Arif Algifari; Wahyudi Ardiansyah; Ilham Gilang Ramadhan (GeoEco, 2024)
This preliminary study explores the hot springs in Padang Ganting, Tanah Datar, West Sumatra, at coordinates 00°34'8.404" S - 100°42'45.716" E and 0°31'26.431" S - 100°45'27.598" E. The research was conducted using geological and geochemical methods in the geothermal field. The collected data includes coordinates of the area, temperature, and pH of the hot springs. The results show a pH distribution ranges from 6 to 7 at several points of the hot springs, with slightly brackish characteristics, and the temperature of the hot springs ranges from 41°C to 51°C. The immature meteoric hot springs originate from the granite formation, indicating the possibility of magma intrusion to the surface, possibly caused by the oroclinal shear segment in the upper part of the Ombilin basin. This study provides a basis for further geological investigations into the geothermal potential and prospects for further development in the geothermal field, contributing to understanding the geological processes in the region.